Biološki zagađivači u zatvorenom prostoru - Radaković, Sonja S.; Marjanović, Milan; Šurbatović, Maja; Vukčević, Gradimir; Jovaševic-Stojanović, Milena; Ristanović, Elizabeta (Vojnosanitetski pregled, 2014)
.